2013
DOI: 10.1089/ars.2012.4566
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bond As a Switch for Copper-Zinc Superoxide Dismutase Activity in Asthma

Abstract: Aim: Loss of superoxide dismutase (SOD) activity is a defining biochemical feature of asthma. However, mechanisms for the reduced activity are unknown. We hypothesized that loss of asthmatic SOD activity is due to greater susceptibility to oxidative inactivation. Result: Activity assays of blood samples from asthmatics and healthy controls revealed impaired dismutase activity of copper-zinc SOD (CuZnSOD) in asthma. CuZnSOD purified from erythrocytes or airway epithelial cells from asthmatic was highly suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…Airway epithelium was obtained by gently brushing the airway, and the freshly obtained cells were immediately processed in the bronchoscopy suite for determination of reduced and oxidized glutathione and reducing potential in human airway epithelium of control subjects and patients with asthma in vivo. Similar to a prior report (4), GSH tended to be higher but GSSG lower in asthma (GSH, mM: patients with asthma, 17 6 3 [n = 3]; control subjects, 8.9 6 0.5 [n = 3]; P = 0.14; GSSG, mM: patients with asthma, 0.38 6 0.04; control subjects, 0.48 6 0.08; P = 0.2), so that the ratio of GSH to GSSG in the airway epithelium of patients with asthma was double that of control subjects (GSH/GSSG: patients with asthma, 43 6 6; control subjects, 20 6 4; P = 0.05) ( Figure 1A). The reduction potential (Eh) of the GSH:GSSG couple calculated by Nernst equation (18,19) revealed a significantly greater intracellular reducing state in the airway epithelium of patients with asthma as compared with control subjects (Eh, mV: patients with asthma, -323 6 4; control subjects, -306 6 3; P = 0.04) ( Figure 1A).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Airway epithelium was obtained by gently brushing the airway, and the freshly obtained cells were immediately processed in the bronchoscopy suite for determination of reduced and oxidized glutathione and reducing potential in human airway epithelium of control subjects and patients with asthma in vivo. Similar to a prior report (4), GSH tended to be higher but GSSG lower in asthma (GSH, mM: patients with asthma, 17 6 3 [n = 3]; control subjects, 8.9 6 0.5 [n = 3]; P = 0.14; GSSG, mM: patients with asthma, 0.38 6 0.04; control subjects, 0.48 6 0.08; P = 0.2), so that the ratio of GSH to GSSG in the airway epithelium of patients with asthma was double that of control subjects (GSH/GSSG: patients with asthma, 43 6 6; control subjects, 20 6 4; P = 0.05) ( Figure 1A). The reduction potential (Eh) of the GSH:GSSG couple calculated by Nernst equation (18,19) revealed a significantly greater intracellular reducing state in the airway epithelium of patients with asthma as compared with control subjects (Eh, mV: patients with asthma, -323 6 4; control subjects, -306 6 3; P = 0.04) ( Figure 1A).…”
supporting
confidence: 84%
“…We have identified that the airway epithelium of patients with asthma is shifted to greater reducing potential, recognized by a higher ratio of reduced to oxidized glutathione (4), which occurs in response to the episodic oxidative inflammation of asthma (1,(5)(6)(7)(8)(9). On this basis, we hypothesized that regional airway inflammation in asthma may be quantitatively evaluated by a nuclear imaging strategy based on uptake of a radiopharmaceutical ( 99m Tc-exametazime [HMPAO]) selectively retained in tissues depending on GSH levels (10-13) (see Figure E1 in the online supplement).…”
mentioning
confidence: 99%
“…In an interesting recent study in asthma patients, disulfidereduced hSOD1 was elevated in human asthmatic erythrocyte and airway epithelial cells, leading to decreased SOD activity in asthma samples (17). The larger fraction of disulfide-reduced hSOD1 in asthma samples was evidenced by the oxidative modification of a disulfide cysteine (Cys-146) upon treatment with H 2 O 2 .…”
mentioning
confidence: 96%
“…19 Another study hypothesized that loss of asthmatic SOD activity is due to greater susceptibility to oxidative inactivation. 20 An increase in ROS generation in asthma and/or COPD patients is confirmed by the changes in the antioxidant …”
Section: Discussionmentioning
confidence: 93%
“…Overall, this study identifies a new paradigm for understanding the chemical basis of inflammation. 20 The difference in mean SOD level was found to significantly decrease among asthmatic patients. 25 Antioxidants not only protect against the direct injurious effects of oxidants, but also alter the inflammatory events that play an important role in the pathogenesis of COPD.…”
Section: Researchmentioning
confidence: 87%